2000
DOI: 10.1152/ajpendo.2000.278.5.e949
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine infusion during moderate intensity exercise increases glucose production and uptake

Abstract: The glucoregulatory response to intense exercise [IE, >80% maximum O(2) uptake (VO(2 max))] comprises a marked increment in glucose production (R(a)) and a lesser increment in glucose uptake (R(d)), resulting in hyperglycemia. The R(a) correlates with plasma catecholamines but not with the glucagon-to-insulin (IRG/IRI) ratio. If epinephrine (Epi) infusion during moderate exercise were able to markedly stimulate R(a), this would support an important role for the catecholamines' response in IE. Seven fit male su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 42 publications
2
25
1
Order By: Relevance
“…Glucose specific activity (SA) was maintained by increasing the tracer infusion incrementally to a maximum of sixfold the rates at rest during the infusion period in CCI and then returning it to the pre-exercise rate in early recovery. The goal was to introduce labeled glucose into the circulation at a rate proportional to endogenous R a , thereby attenuating changes in [ 3 H]glucose SA to Ͻ25% during the rapid changes in glucose kinetics, as in previous experiments (5,6,9,10,22,23). This step would ensure the validity of glucose turnover calculations, even if there were changes in pool fraction during this time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose specific activity (SA) was maintained by increasing the tracer infusion incrementally to a maximum of sixfold the rates at rest during the infusion period in CCI and then returning it to the pre-exercise rate in early recovery. The goal was to introduce labeled glucose into the circulation at a rate proportional to endogenous R a , thereby attenuating changes in [ 3 H]glucose SA to Ͻ25% during the rapid changes in glucose kinetics, as in previous experiments (5,6,9,10,22,23). This step would ensure the validity of glucose turnover calculations, even if there were changes in pool fraction during this time.…”
Section: Methodsmentioning
confidence: 99%
“…Another study (17) with Epi infusion during 40% V O 2max exercise suggested that Epi contributes to, but does not fully account for, the R a increment of IE. Our recent studies of Epi (22) or NE (23) infusions during 50% V O 2max exercise suggest that plasma levels of each could provide a sizable contribution toward the R a increment of IE. Therefore, to test the hypothesis that catecholamines are the primary mediators of the markedly greater R a response to IE than to moderate exercise (ME), we studied the metabolic effects of an incremental combined catecholamine infusion (CCI) designed to approximate the pattern of changes of IE.…”
mentioning
confidence: 98%
“…Therefore, fit normal subjects were exercised for 40 min at 50% VO 2max , and either the individual catecholamines were infused for the last 10 min or both together were infused during the last 14 min. Figure 8 illustrates the effects of EPI infusion at a constant rate that produced circulating concentrations that peaked in the range found in intense exercise (27). This infusion induced rapid increases in GP from the typical twofold increment over resting rates to over half the peak rate of intense exercise (Fig.…”
Section: Effects Of Epi and Ne Infusion Of During Moderate Exercisementioning
confidence: 97%
“…8B). Once again, given the absence of "appropriate" changes in insulin and glucagon during the infusions (27,28,50), virtually the whole of the glucoregulatory responses can be attributed to the levels of catecholamines achieved. These results clearly indicate the capacity of NE and EPI to explain the huge increase in GP of intense exercise.…”
Section: Effects Of Epi and Ne Infusion Of During Moderate Exercisementioning
confidence: 99%
See 1 more Smart Citation